Design and synthesis of indole-thiazole based inhibitors of UDP-galactopyranose mutase - Tie, Ding Yee (2013)
Tuberculosis, which is caused by the pathogenic bacterium Mycobacteria tuberculosis (MTB), is an infectious disease that remains a significant worldwide health threat. Galactofuranose (Galf) residues play an imperative role in the growth of MTB as it is an essential component in the cell wall of this bacterium. UDP-Galactopyranose mutase UGM) is a flavoenzyme that involved in Galf biosynthesis. It catalyzes the reversible conversion of UDP-galactopyranose (UDP-Galp) to UDP-galactofuranose (UDP-Galf). The absence of both UGM and Galf residues in humans make UGM a target for new TB therapeutic drugs. This has also brought us to an interest in UGM. Fourteen potential inhibitors of UGM were identified by alternating the R groups of the structure found computationally, and successfully synthesised in this project. Besides, HPLC assay was carried out to determine the purity of these inhibitors. Subsequently, docking experiments were performed to dock these compounds into the X-ray structure of Deinococcus radiodurans UGM. Further insight of the docking result is evaluated.